COVID-19 treatment guidelines in adults - Pumapillo Garcia, Ana Sarai (2021)
A novel coronavirus disease called COVID-19 was discovered as a result of the outbreak that began in China at the end  of December 2019. Common symptoms are fever, dry cough, shortness of breath and malaise. Several research are being conducted since the disease has high transmission rate even though it is not considered life-threatening. However, together with hospital and out-of-hospital care, there is a group of medications being used to fight this disease, such as hydroxychloroquine, chloroquine, remdesivir, lopinavir/ritonavir, tocilizumab, interferon beta-1b, among others.